The Influence of Leadership Style, Motivation, and Training on Employee Performance - Inna Nisawati Mardiani; Siti Baekhunah (Journal of Research in Business, Economics, and Education, 2021)
Employee performance is a work that can be achieved by a person or group of people in an organization to achieve organizational goals. Leadership style is a way used by a leader in influencing, directing, and controlling the behavior of others to achieve a goal. Motivation is a desire that arises from within employees that creates enthusiasm to work optimally in order to achieve a goal. Job training is all activities that aim to improve and develop work competencies. The purpose of this study was to determine the magnitude of the influence of leadership style, motivation, and job training on employee performance. The object of research at PT Unicraft Nagura Indonesia with a sample of 55 respondents. The method used in this study using multiple linear regression with the help of SPSS software. The results of this study explain that the leadership style variable has a significant effect on employee performance. Motivation variable has no significant effect on employee performance. The training variable has a significant effect on employee performance.